Desain Hypothetical Learning Trajectory (HLT) pada Materi Statistika Konteks Adiwiyata di SD Inpres Waioti - Irma, Maria Ade; Nada, Yohanes H. (Universitas Nusa Cendana, 2024)
This research aims to determine the design hypothetical learning trajectory on statistics material at SD Inpres Waioti.The method used in this research is research design which focuses on developing learning design in form hypothetical learning trajectory. This research is qualitative research using two cycles, namely pilot experiment and teaching experiment. On cycles pilot experiment 4 students were actively involved and teaching experiment involving 12 students. This research was conducted at SD Inpres Waioti. The data collection techniques used were written tests, field notes, and interviews. Meanwhile, data analysis techniques were carried out qualitatively.This research produces something learning trajectory through the PMRI approach which can be used to support the learning process related to statistics, data concentration measures at SD Inpres Waioti class VI. The resulting learning trajectory consists of 7 activities using the PMRI approach as the main or basic reference in every existing activity. The context used in this research is adiwiyata (school that cares and has an environmental culture). Students are asked to observe the school environment with the aim of collecting data directly. Then students are asked to present the data from their observations in tables and bar charts by first sorting the data. The next activity is that students complete the given case and end by determining the mode and median of a data set and finding the formula and determining the mean of a data set